COMPUTER LITERACY AMONG IAIN LHOKSEUMAWE STUDENTS - Wahidah (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2018)
Having certain level in computer literacy is very important to educational setting for students. They should have skill and positive attitudes toward computer to achieve effective teaching and learning process. This study aimedto measure the computing skills, knowledge of IAIN Malikussaleh students about computers, also their attitude toward computers. It is also to determine whether students’ characteristics such as field of study, duration of students’ exposure to computers have significant influence on their computer literacy. From the computation it can be seen that the level of IAIN Malikussaleh students’’ computer skills applied was 4.306 of mean from the highest score of 5 with standard deviation 0.82624 in general. This number indicated that IAIN Malikussaleh students’’ level of computer skill is above average. English and Arabic department students possess quite similar ability or skill in term of computer literacy.The most notable result of this result is the respondents’ attitude toward computer. The respondents who possess good computer skills should have positive attitude toward computer. However, the IAIN Malikussaleh students’ attitude toward computer is average.